PREVALENCE, ASSOCIATED FACTORS AND AWARENESS OF BULLYING AMONG STUDENTS OF PUBLIC AND PRIVATE SCHOOLS OF LAHORE, PAKISTAN - Salman, Fariha; Sharjeel, Muhammad; Abdullah, Mohammad Salman (Pakistan Armed Forces Medical Journal, 2021)
Objectives: To find out prevalence of bullying, its associated factors and extent of awareness against bullying among th students of public/private schools of Lahore and to compare them.Study Design: Comparative cross-sectional study.Place and Duration of Study: Study was carried out in different schools of Lahore, Pakistan, from May to Nov 2019.Methodology: A total of 294 students of public/private schools (8-10th grade students) of Lahore were recruited in study by purposive sampling. The students filled a pretested and pre-structured questionnaire consisting of questions about bullying, number of bullies, forms of bullying, its causes and consequences, reaction of students towards bullying and if anybody was informed about it.Results: A higher frequency of bullying was reported in public schools (54%) than in private (46%). Students mostly suffered bullying in the form of humiliating remarks (56.3%) and verbal abuse (25.3%). Causes of bullying in public schools were physical appearance (48.9%), illness (19.1%) and imbalance of power (19.1%) whereas in private schools, physical status (45.0%), imbalance of power (25.0%) and low socioeconomic status (22.5%) were common. Bullying was associated with loss of concentration on studies (19.5%) and behavioral changes (18.4%). The students usually reported bullying incidents to teachers (36.8%) and parents (28.7%). A majority of students walked away from the bully (45.4%).Conclusion: Bullying is relatively more prevalent in public schools and predominantly manifested in the form of humiliating remarks & verbal abuse. Majority of students show no appropriate resistance towards the bully while bullying causes a critical psychological distress inthem.